URGENSI SOSIALISASI PERATURAN PERUNDANG-UNDANGAN SECARA LANGSUNG MENURUT PERPRES NO.87/2014 DALAM PERSPEKTIF SOSIOLOGI HUKUM - Suherman, Dian Rubiana; Rosmayanti, Lulu Mamlukah (JURNAL ILMIAH OBSGIN : Jurnal Ilmiah Ilmu Kebidanan & Kandungan P-ISSN : 1979-3340 e-ISSN : 2685-7987, 2023)
The existence of the principle of legal fiction creates problems for the application of every statutory regulation in Indonesia, due to the fact that many people at large do not know about the statutory regulations that are currently and will apply in the future. This research was conducted to find out how urgent the direct socialization of laws based on Presidential Regulation Number 87 of 2014 concerning Implementing Regulations of Law Number 12 of 2011 concerning Formation of Legislation in the perspective of legal sociology. This study uses a juridical-normative research method that will use and examine the laws and regulations or positive laws that apply in Indonesia, as well as the implementation of the principles that apply as enforcement of laws and regulations. The sources used in this study are secondary and tertiary legal sources. The results of this research state that the principle of legal fiction is deemed inappropriate or must be intervened by conducting direct socialization to the public as legal subjects. Direct socialization must be carried out to avoid public ignorance regarding laws and regulations which can then ensnare the community itself because of their ignorance. The mechanism for implementing laws and regulations directly through socialization has been regulated in Presidential Regulation Number 87 of 2014, but the implementation is still lacking. In addition, the theory of the sociology of law which says law is a means of social control will not be implemented if the laws itself is not known by society as a whole.